IMPLIKATUR PADA PERCAKAPAN PENJUAL DAN PEMBELI DI PASAR SELASA DESA CINTAMANIS BARU, KECAMATAN AIR KUMBANG, BANYUASIN (KAJIAN PRAGMATIK) - Faizal Yudha Pratama; Hayatun Nufus (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
The problem in this research is how are the general conversational implicatures and the specific conversational implicatures found in the conversations between sellers and buyers at the Tuesday Market, Cintamanis Baru Village, Air Kumbang sub-district, Banyuasin. This study aims to describe, analyze and conclude the conversations between sellers and buyers at Tuesday Market, Cintamanis Baru Village, Air Kumbang District, Banyuasin (pragmatic study). This study uses a qualitative approach with a descriptive type of research. Sources of data in this study are conversations between sellers and buyers at vegetable traders, fish traders, food traders, kitchen equipment traders and fruit traders, while the buyers are housewives in the Pasar Selasa area, Cintamanis Baru Village, Air Kumbang District, Banyuasin. The technique of collecting data in this study used observation techniques, recording techniques, listening techniques, and recording techniques. The results of this study are expected to be useful for other research. From the results of the study, it shows that there are 2 kinds of conversational implicatures between sellers and buyers at Pasar Selasa, Cintamanis Baru Village, Air Kumbang District, Banyuasin (Pragmatic Studies), namely: (a) General Conversation Impliacture Analysis. (b) Special Conversational Implicature Analysis